Nepotism In Organizations: Analysis Of Two Case Studies - Norailis Ab Wahab; Najwa Alyaa Abd. Wakil; Syarizal Abdul Rahim (Academic International Dialogue (AID) Academy, 2024)
Purpose of the study: The issue of nepotism in organizations has long been debated. In fact, the number of articles telling about the phenomenon of nepotism are voluminous which is now considered to be a culture in any organizations. Briefly, nepotism refers to favoritism toward relatives, most commonly in the form of employment offers. The objective of this study is to investigate the advantages of nepotism practices in organisations particularly in Malaysia. Furthermore, nepotism caused by experience and education. These elements are said to be essential in today's contemporary nepotism. Methodology: The methodology applied is qualitative, which are through articles and journals, and in-depth interviews with owners of businesses which are Bismi and MOFAZ that held in 2020. Main Findings: This article present three main findings which are the practice of nepotism in Family-owned Businesses, talent management in organization, employer brand and talent acquisition. Employees of the respective family-owned businesses view the organisations as a source of income, and they understand that the fruit of their hard work is attributed to these employees. In terms of both beneficial and negative consequences in nepotism are exists. Bismi Empire Sdn. Bhd. and MOFAZ (M) Sdn. Bhd. with strong employer brands may readily attract employees that want to work for them. As the employer brands, both organisations offer a variety of benefits to their employees in the form of operational, materialistic, and nonmaterialistic incentives. Novelty of the study: Nepotism is an obstacle that prevents recruiters from attracting the best and brightest candidates in the market which has been described from many viewpoints throughout the existing body of knowledge. However, the findings show different findings based on two cases from two organisations that have long been based in the business world.